The Role of Teachers in Improving Students' Learning Motivation in The Subject of Islamic Culture History in Class IV of MI NU Terpadu - A'yun, Shafa Qurratu; Khasanah, Maungi Dhotul; Purwowidodo, Agus; Huda, Muh. Nurul (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the role of teachers in improving students' learning motivation in the subject of Islamic Cultural History (SKI) in class IV MI NU Terpadu Sumbergempol. The method used is a qualitative approach with a case study type, which allows researchers to investigate in depth the interaction between teachers and students in the context of learning. Data were collected through observation, interviews with the principal, teachers, and students, and documentation. The results of the study indicate that teachers act as effective educators, motivators, and facilitators. Through the use of innovative learning media and varied teaching strategies, teachers are able to create an interesting and enjoyable learning atmosphere. These findings indicate that the active role of teachers is very important in improving student motivation, which in turn contributes to a better understanding of the material of Islamic Cultural History and the development of student character. This study is expected to provide practical contributions for teachers in designing more effective and meaningful learning.